Sympathoexcitation in Rats With Chronic Heart Failure Depends on Homeobox D10 and MicroRNA-7b Inhibiting GABBR1 Translation in Paraventricular Nucleus. (January 2016) - Wang, Renjun; Huang, Qian; Zhou, Rui; Dong, Zengxiang; Qi, Yunfeng; Li, Hua; Wei, Xiaowei; Wu, Hui; Wang, Huiping; Wilcox, Christopher S.; Hultström, Michael; Zhou, Xiaofu; et al.
Abstract : Background—: Chronic heart failure (CHF) increases sympathoexcitation through angiotensin II (ANG II) receptors (AT1 R) in the paraventricular nucleus (PVN). Recent publications indicate both γ-aminobutyric acid B-type receptor 1 (GABBR1) and microRNA-7b (miR-7b) are expressed in the PVN. We hypothesized that ANG II regulates sympathoexcitation through homeobox D10 (HoxD10), which regulates miR-7b in other tissues. Methods and Results—: Ligation of the left anterior descendent coronary artery in rats caused CHF and sympathoexcitation. PVN expression of AT1 R, HoxD10, and miR-7b was increased, whereas GABBR1 was lower in CHF. Infusion of miR-7b in the PVN caused sympathoexcitation in control animals and enhanced the changes in CHF. Antisense miR-7b infused in PVN normalized GABBR1 expression while attenuating CHF symptoms, including sympathoexcitation. A luciferase reporter assay detected miR-7b binding to the 3′ untranslated region of GABBR1 that was absent after targeted mutagenesis. ANG II induced HoxD10 and miR-7b in NG108 cells, effects blocked by AT1 R blocker losartan and by HoxD10 silencing. miR-7b transfection into NG108 cells decreased GABBR1 expression, which was inhibited by miR-7b antisense. In vivo PVN knockdown of AT1 R attenuated the symptoms of CHF, whereas HoxD10 overexpression exaggerated them. Finally, in vivo PVN ANG II infusion caused dose-dependent sympathoexcitation that was abrogated by miR-7b antisense and exaggerated by GABBR1 silencing. Conclusions—: There is an ANG II/AT1 R/HoxD10/miR-7b/GABBR1 pathway in the PVN that contributes to sympathoexcitation and deterioration of cardiac function in CHF. Abstract : Supplemental Digital Content is available in the text.